Parametric investigation on the tensile response of GFRP elements through a discrete lattice modeling approach. (1st November 2019) - Gaetani, Angelo; Fascetti, Alessandro; Nisticò, Nicola
Abstract: Fiber Reinforced Polymers (FRP) are a relatively new construction material. Their attractive features, such as lightness and durability, are currently paving an attractive way for structural engineering applications. However, since their mechanical properties are strongly influenced by the arrangement of the fibers (which is dictated by the production process), more research is still needed to fully characterize the material and to predict its behavior under different multi-axial actions. In this regard, the goal of the present manuscript is to shed light on these aspects by means of numerical analyses according to a lattice modeling approach proposed in (Fascetti et al., 2016) for FRP materials and herein modified to better capture the uniaxial alignment of pultruded elements. Novelty of the work and main contribution to the field is the definition of a numerical procedure for the saturation of the computational domain with different pointsets (i.e. a regular and a random one) in order to increase the accuracy of the method. The proposed approach is validated for tensile loadings, both in terms of mechanical properties and failure modes, through a parametric investigation carried out to simulate the results of the experimental campaign reported in Quadrino et al. (2018) which employed small-scale specimens directly extracted from pultruded glass fiber reinforced polymers (GFRP) beams.